Determination of vulcanization rate constant, crosslink density, and free sulfur content on carbon black flled EPDM - Setyorini, Ike; Yuniari, Arum (Majalah Kulit, Karet, dan Plastik, 2017)
Diï¬erent ethylene propylene diene monomer (EPDM) composite with the carbon black (CB) variation of 50, 60, and 70 phr (per hundred rubbers) is compounded by using an efcient (EV), semi-efcient (SEV), and conventional (CV) sulfur vulcanization systems. This research aims to investigate the eï¬ect of vulcanization systems and carbon black content on the vulcanization rate constant, the crosslink density, and the free sulfur content. This research shows the EV system resulting in the fastest vulcanization rate constant (0.0191/second), the lowest overallcrosslink density (0.0022 mol.cm-3), and the highest percentage of free sulfur content in the EPDM vulcanization (0.40 %). The CV system provides the slowest vulcanization rate constant (0.0061/second) and the highest overall crosslink density (0.0034 mol/cm-3). The percentage of free sulfur content in the EPDM vulcanization of CV system is between EV and SEV systems. The SEV system provides the vulcanization with the characteristic of vulcanization rate constant and overall crosslink density between EV and CV systems as well as provides the lowest percentage of free sulfur content (0.29 %). The higher carbon black loading in each vulcanization systems means the lower rate constant of vulcanization and the higher overall crosslink density.